Kontribusi Koordinasi Mata-Kaki dan Kelincahan terhadap Keterampilan Menggiring Bola Pemain UKM Futsal Kotabaru Usia 18-23 Tahun - Arham Syahban, Jusran S, Sitti Maifa, Hasniah (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2025)
The purpose of this study is to determine the contribution of eye-foot coordination, agility and dribbling skills of Kotabaru Futsal UKM players aged 18-23 years. The research method used is quantitative descriptive with data collection techniques through tests and measurements. The population is Kotabaru Futsal UKM players. The sample used was 27 Kotabaru Futsal UKM players aged 18-23 years. The sampling technique uses random sampling techniques. The results of the study showed that: (1) There was a contribution between eye-foot coordination and the dribbling ability of Kotabaru Futsal UKM players aged 18-23 years by 0.553 or 55.3%. (2) There was a contribution between agility and dribbling ability of Kotabaru Futsal UKM players aged 18-23 years by 0.521 or 52.1%. and (3) there was a contribution between eye-foot coordination and agility with dribbling skills of Kotabaru Futsal UKM players aged 18-23 years by 0.571 or 57.1%. Keywords: futsal, dribbling, eye-foot coordination, agility